1998
DOI: 10.1007/pl00014310
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for homocystinuria: Irish and world experience

Abstract: Newborn screening for cystathionine beta-synthase deficiency (homocystinuria; HCU) was started in the late 1960s using a bacterial inhibition assay (BIA). At least seven countries have either national or regional screening programmes; 12 programmes are known to have discontinued. The worldwide incidence of HCU is approximately 1 in 335,000 but varies from 1:65,000 (Ireland) to 1:900,000 (Japan). Methodologies include the BIA, one-dimensional or thin-layer amino acid chromatography and, more recently, tandem ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 11 publications
0
77
0
2
Order By: Relevance
“…10,18,19,21 To understand the impact of early blood collection in newborn screening, we studied false-negative and false-positive rates in GDSP's blood specimens collected from 12 to 23 hours of age in comparison to the specimens collected from 24 to 48 hours of age. To our knowledge, this is the first study on specimens collected between 12 and 23 hours of age conducted at a population level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,18,19,21 To understand the impact of early blood collection in newborn screening, we studied false-negative and false-positive rates in GDSP's blood specimens collected from 12 to 23 hours of age in comparison to the specimens collected from 24 to 48 hours of age. To our knowledge, this is the first study on specimens collected between 12 and 23 hours of age conducted at a population level.…”
Section: Discussionmentioning
confidence: 99%
“…The other concern is the potential increase of false negatives (true cases reported as negative screening results). 19,20 The primary concern is with disorders of amino acid metabolism, where early collection could mean that the newborn's metabolism has not been functioning independently for long enough for the metabolic disorder to be evident from Purpose: The current Clinical and Laboratory Standards Institute standard recommends blood collection from 24 to 48 hours after birth for newborn genetic disorder screening. We used California population-level data to determine whether early specimens (collected from 12 to 23 hours) would also be considered satisfactory based on screening performance.…”
Section: Introductionmentioning
confidence: 99%
“…Screening for the aminoacidopathies maple syrup urine disease, homocystinuria and tyrosinaemia using leucine/ isoleucine, methionine and tyrosine, respectively, is known to be problematic with high rates of false-positive screening and missed cases being reported (Estrella et al 2014;Naughten et al 1998). In fact many patients with these conditions can have normal metabolites at the time of newborn screening (https://www.clir-r4s.org/ProjTools/DiseaseRangeComp.aspx) and thus these conditions were not part of this study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from New England showed that lowering the cutoff level for blood methionine from 134 to 67 µmol/l almost doubled the reported incidence of homocystinuria (Peterschmitt et al, 1999). This notion suggests that in various populations the previously determined incidence that employed cutoff levels as high as 270 µmol/l (Naughten et al, 1998) may have underestimated the frequency of this disease. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Two major phenotypes of this autosomal recessive disease are equally common, a milder pyridoxine-responsive form, and a more severe non-responsive type. However, treatment with pyridoxine, methionine-restricted diet or betaine prevents the development of somatic and mental abnormalities in the more severe forms only when started in infancy (Naughten et al, 1998;Walter et al, 1998). Such a favorable outcome in early treated patients, and a possibility to diagnose the disease from blood spots rank homocystinuria among inborn errors of metabolism that would benefit from newborn screening.…”
Section: Introductionmentioning
confidence: 99%